STUDI EMPIRIS FAKTOR-FAKTOR YANG MEMENGARUHI PERILAKU DISFUNGSIONAL AUDIT - Istiqomah.P.P, Sarah Fitriani; Y, Rahmawati Hanny (Jurnal Akuntansi, 2017)
This study aims to examine and analyze the locus of control, turnover intention, time budget pressure, the performance auditor, leadership styles, organizational commitment to audit dysfunctional behavior. This type of research in this research is qualitative research. The population in this study is the auditors who work in public accounting firms throughout Jakarta. The sampling technique in this study were selected through purposive sampling technique. The number of samples in this study is 32 KAP with 256 respondents. Analysis data are using regression analysis. The result of this research is the locus of control, turnover intention,time budget pressure, and performance have an influence on the behavior of dysfunctional audit. Leadership style and organizational commitment has no effect on audit dysfunctional behavior. And locus of control, turnover intention, time budget pressure, the performance auditor, leadership style and organizational commitment together have an influence on the behavior of dysfunctional audit.